Innovative strategies in islamic education management facing the era of global disruption - Febrianty Eka Putri; Roihan Sadad (At Turots: Jurnal Pendidikan Islam, 2025)
The era of global disruption characterized by rapid technological advances, socio-cultural paradigm shifts, and dynamic economic changes, presents significant challenges and opportunities for Islamic education. This research explores innovative strategies in the management of Islamic education institutions that aim to adapt to educational transformation while maintaining Islamic values. Emphasizing on strategic leadership, curriculum innovation, digital integration and stakeholder collaboration, this study highlights how Islamic education can remain relevant, competitive and transformative. Through qualitative analysis and case studies, this research identifies best practices that align the goals of Islamic education with the demands of a globalized and digitized world. The findings suggest that a proactive, adaptive and visionary approach to education management is essential to cope with disruption and sustain students' holistic development in accordance with Islamic principles.